Loboforenos inéditos obtidos da alga parda Lobophora variegata com atividade citotóxica em células tumorais e moduladora da resposta inflamatória de macrófagos - Ferreira, Kayanny Queiroz (2018)
The Lobophora variegata macroalgae is rich in omega-3 fatty acids, calcium, phosphorus and vitamin C, being a species that has antioxidant, antitumor and anti-inflammatory effects. Inflammation is a fundamentally protective response of the host in response to an infection or aggression. However, prolonged inflammation is associated with a variety of progressive diseases such as metabolic disorders, neurodegenerative diseases, cardiovascular diseases and cancer. New substances with anti-inflammatory potential are of great clinical relevance, since the traditional approach to the treatment of chronic inflammation is costly and generates side effects that decrease patients' quality of life. Additionally, the association of antineoplastics with modest potency cytotoxic compounds and anti-inflammatory effect, such as omega 3 fatty acid, improves the antitumor response while reducing some of the side effects. The objective of this study was to evaluate the cytotoxicity and modulation of the activation of macrophages stimulated with bacterial lipopolysaccharide by substances extracted from L. variegata using in vitro models. The cytotoxicity of compounds extracted in hexanic, acetate and ethanolico solvent was evaluated against colon adenocarcinoma cells (HCT 116 strain), the most potent hexanic extract having an average inhibitory concentration (IC50) value of 5.4 μg / mL. Eleven compounds of the hexanic extract were isolated, with 2 unpublished polyunsaturated henoecosanic epoxides, 1 and 2. The structures of the lobophorenes share similarities with polyunsaturated fatty acids such as omega-3 and -6 and arachidonic acid. Lobophorenes were moderately cytotoxic against HCT 116 with a mean inhibitory concentration (IC 50) of 8.6 μM and 8.1 μM, respectively. The anti-inflammatory potential was investigated in macrophage lineage (RAW264.7). Macrophages were pretreated with 1 and 2 at concentrations of 3.5 and 35 μM for 1h and then stimulated with LPS. The Griess assay was performed to indirectly dose nitric oxide (NO); ELISA to measure the production of cytokines in addition to the detection of the transcription factor NF-κB by immunoblot. Compounds 1 and 2 at concentrations of 35 μM completely inhibited the production of nitrite and IL-6, since both concentrations inhibited 50% IL-1β and above 80% TNF-α production. There was total inhibition of IL-10, anti-inflammatory cytokine, at 35 μM concentration by compound 1 and more than 80% in compound 2, and at concentrations of 3.5 μM there was no inhibition. Both compounds inhibited NF-κB expression at concentrations of 3.5 and 35 μM and showed antioxidant activity at 35 μM. Thus, in the present work, 2 unpublished loboforenes isolated from the L. variegata alga were identified with moderate potency cytotoxicity and macrophages activation modulating effect in vitro.